Pembrolizumab-combination therapy for NSCLC- effectiveness and predictive factors in real-world practice - Knetki-Wróblewska, Magdalena; Dziadziuszko, Rafał; Jankowski, Tomasz; Krawczyk, Paweł; Bryl, Maciej; Stencel, Katarzyna; Wrona, Anna; Bandura, Artur; Smok-Kalwat, Jolanta; Rok-Knapińska, Jolanta; Szydziak-Zwierzyńska, Kinga; Rogoziewicz, Krzysztof; et al. (Frontiers in Oncology, 2024)
Pembrolizumab combined with chemotherapy has become the standard of care for patients with nonsmall-cell lung cancer (NSCLC) and the expression of programmed death ligand 1 (PD-L1) in <50% of tumour cells (TC). Although patients with low PD-L1 expression (<1%) are also treated, there are different viewpoints on the effectiveness of this combination. Therefore, we evaluated the value of pembrolizumab in combination with chemotherapy in patients with low PD-L1 expression in the real world. We evaluated the efficacy of the treatment in real-world practice, paying attention to the predictive factors, with a special focus on low level of PD-L1 expression. This study is a multicenter retrospective analysis of patients with stage IV NSCLC treated in routine practice. A group of 339 consecutive patients was analysed, among them 51% patients with low PD-L1 expression. In the overall population, the ORR was 40.6%, median PFS and OS were 13 months (95% CI 11.4-15) and 16.8 months (95% CI 13.3-20.3), respectively. In multivariate analysis for the entire study population, performance status -ECOG 1 vs. 0 (HR 2.2, 95%CI 1.1-4.6; p=0.02), neutrophil to lymphocyte ratio (NLR)>3 (HR 2.3, 95%CI 1.3-4.2; p=0.04), presence of liver (HR 2.0, 95%CI 1-3.7; p=0. 03) and bone metastases (HR 1.3, 95%CI 1-3; p=0.04), weight loss (HR 1.8, 95%CI 1.1-2.8; p=0.01) and sum of measurable lesions diameters >110 mm (HR 1.7, 95%CI 1-2.9, p=0.049) had a negative impact on OS. In the real world, patients can clinically benefit from immunochemotherapy, regardless of the expression of PD-L1 and the histological type. Other clinicopathological factors such as performance status, extent, and location of secondary lesions have prognostic significance.